Experimental Investigation Of Electrical Discharge Machining Using Dielectric Fluid With Surfactant And Different Carbon Additives - Liew, Pay Jun; Abdul Razak, Muhammad Raziman; Hussein, Nur Izan Syahriah; Ahsan, Qumrul (Research India Publications, 2016)
In this paper, Electrical Discharge Machining of Reaction Bonded Silicon Carbide (RB-SiC) was carried out using dielectric fluid with different surfactant concentrations and different type of carbon additives. Surfactant concentrations and types of carbon additives were varied and the machining performances such as material removal rate (MRR), electrode wear ratio (EWR), surface roughness and spark gap were investigated. The experiment results show that the surfactant and carbon additives added dielectric fluid not only increases the MRR and spark gap, but also reduces the EWR. In the case of surface roughness, only 0.4 wt.% surfactant with CNF produced smoother surface compared to the one obtained with no surfactant. Among three carbon additives, CNF was more effective to improve the machining efficiency of RB-SiC with the optimum surfactant concentration at 0.6 wt.%.